MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS KINERJA TENAGA KEPENDIDIKAN DI SD NEGERI - Asmawati, Asmawati; Mulyadi, Said; Rizki, Sari (Hijri, 2024)
The aim of this research is to describe the leadership management of school principals in improving the quality of performance of education staff at SD Negeri 3 Dewantara, North Aceh Regency. This research uses qualitative methods that are field research. There were four informants. The research findings show that the principal's leadership planning in improving the quality of performance of educational staff at SD Negeri 3 Dewantara is carried out by preparing plans for increasing educational staff by basing it on the school's vision, mission and goals based on needs analysis and job position analysis. Organizing the performance of educational staff, namely the preparation and formation of working relationships between the management components of the school's organizational structure that have been determined, and determining the main tasks of educational staff in accordance with their position or profession. Leadership of the school principal in improving the quality of the performance of educational staff is carried out by involving educational staff in scientific forums. (seminars, training, workshops, workshops and courses), welfare benefits, provision of supporting facilities such as provision of computers or laptops that can access the internet to access new information. Evaluation in improving the quality of performance of educational staff by carrying out educational supervision. The aspects evaluated are the presence of educational staff, the performance of educational staff, achievements and the school principal also carries out an assessment using an assessment format that has been standardized by the government, known as the Performance Assessment List (DP3).